Queer Cultural Movements and Local Counterpublics of Sexuality: a Case of Seoul Queer Films and Videos Festival - Kim, Jeongmin; Hong, Sunghee (Inter-Asia Cultural Studies, 2007)
This study is an attempt to examine the ways in which popular culture can restructure the relationship between sexuality and power, through the case of Seoul Queer Films and Videos Festival, a cultural arena of newly emerged queer discourses in Korean society. In the past 10 years, queer discourses in Korea have undergone a rapid change. With heterosexual normativity being challenged and ‘queer’ being consumed as a cultural code, Korean spectators come to engage with a queer film festival in multilateral and sometimes contradictory contexts. This study will try to pose a controversial question to the heterosexual society by reading the complex interactions between film festivals, films and spectators while paying attention to the experiences of the participants in the Seoul Queer Films and Videos Festival and pointing at the political implications of queer films now in 2006. Through this, I try to look for possibilities of a queer cultural movement which rejects being co‐opted by the heterosexual society, constructs new ideas of social powers in relation with sexuality, and seeks alternative visions for such change in relations.
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Asie (corpus analysé); _Nettoyé